Orghanophosphate food poisoning in a family in Mukim Rantau, Negeri Sembilan - Omar M; Rozali A; Sherina MS; Rosnah I (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Organophosphates are used in large quantities around the world as agricultural pesticides. They are well documented as a cause of acute poisoning in humans including suicidal ingestion, occupational exposure and unintentional exposure through inhalation, skin absorption and ingestion. This is a report of an incident of organophosphate food poisoning in a family residing in Mukim Rantau, Negeri Sembilan. The victims (three males and one female) were aged between 32 to 60 years old. All suffered from symptoms of severe acute food poisoning such as nausea, vomiting, diarrhoea, sweating, confusion, headache, difficulty in breathing and muscle weakness ajier taking their dinner. The female victim died one hour after developing symptoms. The other three were admitted to the hospital. Investigation revealed 'fried lady's fingers' as a suspected source with possibility of cross contamination occurring during preparation of the meal. The suspected chemical substance was pesticide containing organophosphate, based on classical symptoms and signs of acute organophosphate poisoning, severe low levels of serum cholinesterase, good response to treatment with intravenous atropine, evidence of pesticide use in the patients' plantation, and post mortem results of organophosphate substance in the deceased's stomach content.